Trends and Determinants of Sustainability Sukuk Issuance: Evidence from Global Markets - Nazrul Hazizi Noordin (Journal of Islamic Monetary Economics and Finance, 2026)
Despite the growing prominence of sustainability sukuk in the global realm of sustainable finance, little is known about the dynamics of their issuance. This study is the first to document the evolution of sustainability sukuk issuance and explore the determinants of its size. Using a cross-country sukuk dataset comprising 11,944 issuances between 2012 (i.e., the year when the first sustainability sukuk was issued) to 2022, it highlights that sustainability sukuk remains a minuscule fraction of overall sukuk markets, and its rapid growth during the last recent years is mostly concentrated in Islamic finance-oriented countries like Indonesia, Malaysia, and Saudi Arabia, while other developing Muslim-majority nations show limited participation. Examining determinants, we find that a higher security quality, a more extended debt structure, and major international currency denominations (e.g., USD and Euro) positively influence the size of the sustainability sukuk issue. Additionally, we uncover two unique drivers of sustainability sukuk issuance. The first is second party opinion, where its increased costs reduce issue size. The second is the underlying equity-based Islamic contracts, which encourage larger issuances compared to sale-based contracts. Our results also indicate that issuances by government entities and financial institutions, and those raised for social purposes rather than green projects, tend to be larger. Lastly, we find that a higher level of economic development and greater reliance on international trade in the issuing country may lead to a larger issue size. This paper concludes by calling for policies and incentives to encourage future sustainability sukuk issuance.